2019
DOI: 10.1002/jcp.28394
|View full text |Cite
|
Sign up to set email alerts
|

FGF10 enhances yak oocyte fertilization competence and subsequent blastocyst quality and regulates the levels of CD9, CD81, DNMT1, and DNMT3B

Abstract: The fusion of sperm and oocytes determines the fertilization competence and subsequent development of embryos, which, in turn, can be affected by various proteins and DNA methylation. However, several factors in this whole regulation process remain unknown, especially in yaks. Here, we report that fibroblast growth factor 10 (FGF10) is an important growth factor that can enhance the maturation rate of yak oocytes and the motility of frozen spermatozoa. Subsequent blastocyst quality was also improved by increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Consistently, as shown in Figure 3a, this study showed that CD9 protein expressed in oocytes of cattle during maturation. Previous studies showed that CD9 protein expression in mouse oocytes at GV stage was significantly higher than that that at other stages (Komorowski et al, 2006; Pan et al, 2019). While in porcine oocytes, CD9 protein expression in MII porcine oocytes was higher than in that in GV and MI oocytes (Li et al, 2004).…”
Section: Discussionmentioning
confidence: 89%
“…Consistently, as shown in Figure 3a, this study showed that CD9 protein expressed in oocytes of cattle during maturation. Previous studies showed that CD9 protein expression in mouse oocytes at GV stage was significantly higher than that that at other stages (Komorowski et al, 2006; Pan et al, 2019). While in porcine oocytes, CD9 protein expression in MII porcine oocytes was higher than in that in GV and MI oocytes (Li et al, 2004).…”
Section: Discussionmentioning
confidence: 89%
“…At the same time, the FGF10 mRNA concentration in the ovaries of healthy and growing bovine follicles was higher than that in atresia follicles ( Buratini et al, 2007 ), which indicated that FGF10 played an inhibitory role in early follicular development and promoted follicular maturation in late follicular development. FGF10 can also regulate the expression of genes CD9 , CD81 , DNMT1 , and DNMT3B to improve embryo quality ( Pan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the expansion of TE in early development depends on FGF in mice, and that this expansion, which is dependent on FGF, occurs more in late stages in humans. The actions of FGF family members begin in the initial steps of reproduction mechanisms, therefore, FGF-10 expression has been detected in theca cells and ovarian stromal cells in humans [ 88 ], and FGF-2 and FGF-10 have been shown to increase the survival and proliferation of cumulus cells, increasing blastocyst development rates in bovine, sheep, and yak, in in vitro cultures [ 89 , 90 , 91 , 92 ]. Another family member, FGF-18, seems to regulate steroidogenesis in the fetal ovary [ 93 ].…”
Section: Growth Factors and Early Developmentmentioning
confidence: 99%